Development of Chalk from Selected Herbs as Cockroach (Periplaneta americana) Repellents - Raphael Kevin Nagal (Philippine Association of Institutions for Research, Inc., 2019)
The World Health Organization (WHO) estimates that there are 3 million cases of pesticide poisoning each year and up to 220,000 deaths primarily in developing countries. Commercial repellents and pesticides, aside from being expensive, also contain chemicals that, when ingested, may pose further threats to the health of humans. The study aims to determine which plant preparation (bay leaf, garlic, peppermint, eucalyptus at 25%, 50% and 75% each) were able to form chalk and can repel the P. americana. Endemic and accessible plants namely, eucalyptus (Eucalyptus globulus), garlic (Allium sativum), peppermint (Mentha piperita), bay leaf (Laurus nobilis) were used in this study as Periplaneta americana repellent in the form of chalk. Using a Completely Randomized Design, results revealed that the type of plant preparation and chalk formation are independent. All plant preparations repelled the P. americana. Based on the means of distances (cm) of repulsions, it was revealed that 75% Peppermint preparation has the highest repulsion mean of 80.67cm based on three trials. Hence, it is highly suggested that 75% and 50% Mentha piperita, as well as 75% Eucalyptus globulus, should be manufactured for commercial production based on the results of this study.